2006
DOI: 10.1002/gps.1567
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for neuropsychiatric symptoms in dementia: the Cache County Study

Abstract: Gender, age, dementia severity, APOE epsilon4, dementia diagnosis, time of observation, and general medical health appear to influence the occurrence of individual neuropsychiatric symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
95
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(107 citation statements)
references
References 43 publications
8
95
1
3
Order By: Relevance
“…Although the influence of female gender on the factor score for affective symptoms was similar to that observed in previous studies [26], the involvement of ADL in affective symptoms was a notable finding. This finding reflects the fact that the patients in our study often presented with severe depression and difficulty with food intake which required hospitalization and intravenous nutrition.…”
Section: Discussionsupporting
confidence: 86%
“…Although the influence of female gender on the factor score for affective symptoms was similar to that observed in previous studies [26], the involvement of ADL in affective symptoms was a notable finding. This finding reflects the fact that the patients in our study often presented with severe depression and difficulty with food intake which required hospitalization and intravenous nutrition.…”
Section: Discussionsupporting
confidence: 86%
“…The finding that physical health is associated with depression in Vascular Dementia but not in AD (Ballard et al, 1996) supports this conclusion. A previous study of prevalent dementia from this population (Steinberg et al, 2006) found worse general health to be associated with agitation, irritability, disinhibition, and aberrant motor behavior. In contrast to the present focus on incident AD cases, differences in results may reflect the inclusion of other forms of dementia and greater disease severity and longer dementia duration associated with prevalent samples in the previous study.…”
Section: Discussionmentioning
confidence: 59%
“…Evidence suggests that between 60% and 90% of individuals with AD experience at least one disturbance during the course of their illness (e.g., Steinberg, 2006;Ikeda et al, 2004;Brodaty et al, 2001). They contribute to greater caregiver and patient distress (e.g., Craig et al, 2005;Danhauer, 2004), more costly interventions (e.g., Beeri et al, 2002;Finkel, 2000), and accelerated cognitive and functional decline (e.g., Boyle et al, 2003;Copeland et al, 2003;Holtzer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations